Comparative study on production of α-Amylase from Bacillus licheniformis strains - Divakaran,Dibu (2011)
Alpha amylase (α-1, 4-glucan-glucanhydrolase, EC 3.2.1.1), an extracellular enzyme, degrades α, 1-4 glucosidic linkages of starch and related substrates in an endo-fashion producing oligosaccharides including maltose, glucose and alpha limit dextrin (7). The present study deals with the production and comparative study of production of α-amylase from two strains of Bacillus licheniformis, MTCC 2617 and 2618, by using four different substrates, starch, rice, wheat and ragi powder as carbon source by submerged fermentation. The effect of varying pH and incubation temperature, activator, inhibitor, and substrate concentration was investigated on the activity of α-amylase produced by MTCC strain 2618. The results shows that the production of the α-amylase by the B.licheniformis strain MTCC 2618, using four different substrates were found to be maximum (Starch 3.64 IU/ml/minutes, Rice powder 2.93 IU/ml/minutes, Wheat powder 2.67 IU/ml/minutes, Ragi powder 2.36 IU/ml/minutes) on comparing the enzyme production of two strains. It was also observed that the maximum production was found on the 3rd day (i.e. 72 hr) and characterization of crude enzyme revealed that optimum activity was at pH 7 and 37ºC.